DMP1-mediated transformation of DPSCs to CD31+/CD144+ cells demonstrate endothelial phenotype both in vitro and in vivo - Ganapathy, Amudha; Chen, Yinghua; Bakthavachalam, Velavan; George, Anne (Frontiers in Cell and Developmental Biology, 2025)
IntroductionDental pulp stem cells (DPSCs), can differentiate into endothelial cells (ECs), offering a promising strategy for generation of new blood vessels which is crucial for tissue repair and regeneration. Many studies have focused on optimizing conditions for differentiating DPSCs into ECs in vitro and subsequent validation of the vasculogenic potential of newly generated ECs in vivo. Previously, we demonstrated the ability of the HUVEC ECM scaffold along with DMP1 stimulation would drive endothelial-specific lineage of DPSCs.MethodsIn this study, DMP1-treated DPSCs were cultured on HUVEC ECM for 7 days and sorted using angiogenic-specific markers CD31 and CD144. The cells were separated into a positive fraction (CD31+/CD144+) and a negative fraction (CD31−/CD144−). To assess if ECs transformed from DMP1 stimulated DPSCs maintain their endothelial properties over time, we cultured both the positive CD31+/CD144+ and negative CD31−/CD144− fractions along with unstimulated DPSCs and assessed their angiogenic characteristics by gene expression analysis, functional properties using a tubule formation assay and in vivo subcutaneous implantation model.Results and discussionThe findings of this study indicate that the CD31+/CD144+ fraction, retains both the phenotypic and functional characteristics of ECs, in contrast to the CD31−/CD144− fraction. Furthermore, in vivo analysis of the sorted ECs using the subcutaneous implantation model exhibited neovascularization along with the expression of vasculogenic markers. Overall, DPSC-derived ECs obtained by stimulation with DMP1 and cultured on HUVEC-ECM function as typical vascular ECs. This strategy, could be exploited for the development of vasculogeneis and as a therapeutic potential for tissue repair and regeneration.